Perform Strikes. A Case Study - Malo, Enrico Mora (Qualitative Sociology Review, 2009)
In this paper we show the results of an analysis of the production of individual class subjectivities in the context of strikes among both those in favour and those against. Among the several processes going on in the production of subjectivities of class, we consider strikes because we want to emphasise the active role that the subjects keep up within the class relationships of domination and exploitation. We start from a conception of the subjectivity understood as fragmentary and contingent that we apply to our analysis of class, but in this paper we limit production of individual subjectivities to context of strikes. Our analysis focuses on a case study from the beginning of the 1970s to the end of the 1990s, which was led by the workers of a company in the motor industry, situated in Catalonia. The main devices used to work on the empirical material are biographical interviews and informative interviews. We start the analysis by showing the various directions taken by that the subjectivities of workers and of the company in strike interactions, in individual terms. Then we look into the role of gender in the provisional configuration of these subjectivities in the context of a strike when these subjectivities became collective subjectivities. In this respect, we focus on the company’s workers.